ADOPTION OF BLENDED LEARNING INTO THE NIGERIAN EDUCATION SYSTEM: PROSPECTS AND CHALLENGES - Oghenevwede, Regha Israel (PEOPLE: International Journal of Social Sciences, 2015)
Technology-mediated learning is a generic term which encompasses different teaching and learning approaches that is supported by the use of Information and Communication Technologies (ICTs). Technology-mediated learning has in several ways contributed significantly to the advancement of education globally. The advantages it offers are being leverage on by governments and educational institutions world over to improve on the quality and quantity of education in the most efficient and cost effective way. One example of a technology-mediated learning is blended learning. Blended learning is defined as a teaching and learning approach that combines online learning and face-to-face instructions in the most effective way for optimal learning outcome. This paper discussed the meaning and benefits of blended learning and ways some of these advantages could be used to reduce the many challenges facing the Nigeria educational system. Reduced cost on expansion and maintenance of infrastructures, improved safety of lives and properties in schools, reduction in national illiteracy level are some of the identified prospects. While poor power supply, inadequate skilled man power, poor internet connectivity and corruption by government officials are among the identified challenges of adopting blended learning into the Nigerian educational sector. The paper recommended organisation of seminars/workshops/trainings, setting up of pilot study centres, collaboration with international institutions among others, as strategies that would enhance effective adoption of blended learning into the Nigeria education system.